Prienų šnektos žemutinių balsių kiekybė ir kiti skiriamieji bruožai - Jaroslavienė, Jurgita (Baltistica, 2006)
THE QUANTITY AND OTHER DISTINCTIVE FEATURES OF LOW VOWELS IN THE SUBDIALECT OF PRIENAI Experimental investigation of the quantity, quality and other distinctive features of the low non-short vowels in the subdialect of Prienai has shown that vowels of different origin are characterised by different acoustic and articulatory features. The measurement of vowel duration has indicated that [a˙] <*-añ-, [e˙] ([æ]) <*-eñ- are longer than those lengthened due to the stress by the ratio of 1.29 : 1. For this reason they were considered as long and half-long vowels respectively. This has been attested by statistical evaluation, too. Qualitative differences have also been revealed between low long and half-long vowels. The timbre of back low [a˙] is lower than that of [a.]. The variable articulation is typical of the front low vowels [e˙] and esp. [æ˙]. At the beginning of the sound the timbre of [e˙] and [æ˙] is slightly higher than the timbres of [e.] and [æ.], while at the end the slightly lower timbre is typical of [e˙] and [æ˙].